Metabolic profiling of luteolin‐7‐O‐glucoside in rat urine, plasma, bile and feces after oral administration using ultra‐high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry. (10th January 2016) - Liu, Hongxia; Huo, Xiaoguang; Ding, Liqin; Feng, Xinchi; Jiang, Miaomiao; Pan, Guixiang; Chen, Lixia; Qiu, Feng
Abstract : Rationale: Luteolin‐7‐ O ‐glucoside (L7G), the main bioactive ingredient of Chinese Lantern, has various biological functions, including anti‐inflammatory and anti‐oxidative activities. However, research on luteolin‐7‐ O ‐glucoside has focused on the extraction, separation and biological activities of this natural product, whereas the metabolism of luteolin‐7‐ O ‐glucoside in vivo is not fully understood. In order to explore the metabolic profile of luteolin‐7‐O‐glucoside, we investigated its metabolites in plasma, bile, urine and feces samples following oral administration to rats. Methods: In this study, an ultra‐high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry (UPLC/QTOFMS) method with a workflow‐interpretation strategy was developed to profile and identify the major metabolites of luteolin‐7‐ O ‐glucoside in rat urine, plasma, bile and feces after oral administration. Results: A total of 44 luteolin‐7‐ O ‐glucoside‐related metabolites were identified in rat biological samples after oral administration of luteolin‐7‐ O ‐glucoside, including 35 metabolites in urine, 17 metabolites in plasma, 17 metabolites in bile and 5 metabolites in feces. Additionally, three major metabolites (M22, M40 andM44 ) were isolated as standards from urine and feces. Conclusions: The study indicated that luteolin‐7‐ O ‐glucoside was hydrolyzed to luteolin firstly, and then for further absorption, metabolism and excretion in viv o. The results showed that phase I metabolites are hydrolysis and reduction metabolites, and phase II metabolites include sulfation, glucuronidation and methylation metabolites. This research provides scientific and reliable support for full understanding of the metabolic profiling of luteolin‐7‐ O ‐glucoside and the results provide evidence that should help to elucidate the effective substance basis of luteolin‐7‐ O ‐glucoside in vivo . Copyright © 2016 John Wiley & Sons, Ltd.